Anaesthesia Type, Gender and Anxiety. Issue 3 (March 2013) - Mitchell, Mark
The number of patients treated by elective day-case surgery in the UK is growing. Patient preoperative anxiety can be considerable, although the opportunity to help to reduce fears is minimal. Day surgery patients (n=674) were surveyed and 82% were found to be anxious. General anaesthesia patients were more anxious than local anaesthesia patients and females more anxious than males. The results indicate that general anaesthesia patients may require more preoperative information, and gender differences associated with waiting may need to be given greater consideration.